Customer engagement and social media research - Anwar, Kendis; Abror, Abror; Batubara, Hani Maisyarah; Astuti, Kristiana; Sari, Nadhila (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
One of the key challenges for food and beverage marketers is how to effectively garner engagement with their content (e.g., liking, commenting, and sharing) in an effort to increase audience exposure on the platform and improve business performance. The purpose of this research is to find out the dominant methods, issues, and problems of social media. It can be said that the method used is quantitative, and the social media used is Facebook. Based on the results of the research, it is found that the problem or issue that occurs is that consumer engagement can improve relationships with consumers, which is realised in the form of consumer participation, which is the driving force behind online sales and brand success. This is the source of most of the problems that arise. This also means that companies using social media to promote their brands need to have a more intimate relationship with the people they want to reach, which is based on trust, social relationships, image, and identity on social media. Fulfilling a company's commitment to its customers is another important responsibility. This will build trust and confidence in customers, which in turn encourages them to participate more actively in a brand's social media activities.